2022
DOI: 10.3390/antib11030057
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Characterization of a Broadly Neutralizing Anti-SARS-CoV-2 Antibody Isolated from a Semi-Immune Phage Display Library

Abstract: Neutralizing antibodies targeting the receptor-binding domain (RBD) of SARS-CoV-2 are among the most promising strategies to prevent and/or treat COVID-19. However, as SARS-CoV-2 has evolved into new variants, most of the neutralizing antibodies authorized by the US FDA and/or EMA to treat COVID-19 have shown reduced efficacy or have failed to neutralize the variants of concern (VOCs), particularly B.1.1.529 (Omicron). Previously, we reported the discovery and characterization of antibodies with high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…However, it decreased significantly in the group treated with 5 mg/kg ( p = 0.001), indicating a protective effect at that higher dose. The efficacy of IgG-A7 at 0.5 mg/kg against Delta infection and a ten-fold higher dose (5 mg/kg) against Omicron correlated with the neutralization potency of IgG-A7 in PRNT [ 6 ], showing that IgG-A7 had a lower NC 50 for Omicron (2.93 nM) than for Delta (0.06 nM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it decreased significantly in the group treated with 5 mg/kg ( p = 0.001), indicating a protective effect at that higher dose. The efficacy of IgG-A7 at 0.5 mg/kg against Delta infection and a ten-fold higher dose (5 mg/kg) against Omicron correlated with the neutralization potency of IgG-A7 in PRNT [ 6 ], showing that IgG-A7 had a lower NC 50 for Omicron (2.93 nM) than for Delta (0.06 nM).…”
Section: Resultsmentioning
confidence: 99%
“…The SARS-CoV-2 Delta and Omicron viruses were isolated and characterized as described in González-González [ 6 ]. The whole genome sequences of these SARS-CoV-2 strains are deposited in GenBank with the following accession numbers: OM060237 (Delta) and ON651664 (Omicron).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro viral neutralization assays were performed as previously described [ 92 ] using a clinical isolate of SARS-CoV-2 (GenBank: OL790194). Briefly, cultures of Vero CCL81 cells (50,000 cells/cm 2 ) were seeded into 24-well plates, and the next day, the cells were exposed for 1 h to subtoxic concentrations of the Mpro inhibitors prepared in serum-free EMEM.…”
Section: Methodsmentioning
confidence: 99%
“…An antibody cocktail therapy targeting the RBD has achieved specific results [ 7 ]. Indeed, Mendoza-Salazar and González-González et al reported that a phage display single-chain fragment variable (scFv) blocks binding of the RBD to human ACE2, suggesting these antibodies may neutralize SARS-CoV-2 infection [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%